2016
DOI: 10.4269/ajtmh.15-0310
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blood Transfusions in Anemic Children in Effia Nkwanta Regional Hospital, Sekondi-Takoradi, Ghana

Abstract: Abstract. Blood transfusion is a common practice in sub-Saharan Africa as a way of correcting anemia in children with mild and severe sicknesses. This study evaluated this practice in a secondary health-care institution in Ghana. A retrospective study was done over a 3-year period from January 2010 to December 2012. Medical records of children admitted, successfully treated, and discharged from the hospital were collected and analyzed. Data were analyzed using Epi Info version 7. Transfusions were more among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
6
9
1
Order By: Relevance
“…We found parallel patterns both for the individual hospital wards, with most products being given to the pediatric ward, and for subgroup patient populations. In the pooled analysis of the nine studies that included only children, it was found that 64% of blood products were used for children with severe malaria. Similarly, from the five pooled studies in obstetrics and gynecology, over one‐half (54%) of blood products were used for obstetric hemorrhage (represented here by the diagnostic categories of PPH, antepartum hemorrhage, and cesarean deliveries).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We found parallel patterns both for the individual hospital wards, with most products being given to the pediatric ward, and for subgroup patient populations. In the pooled analysis of the nine studies that included only children, it was found that 64% of blood products were used for children with severe malaria. Similarly, from the five pooled studies in obstetrics and gynecology, over one‐half (54%) of blood products were used for obstetric hemorrhage (represented here by the diagnostic categories of PPH, antepartum hemorrhage, and cesarean deliveries).…”
Section: Discussionsupporting
confidence: 85%
“…Blood use among the other patient populations of pediatrics, obstetrics and gynecology, cesarean section births, and newborns are shown in Appendices S3.3 through S3.7. The studies among pediatric patients showed that 64% (2810 of 4387) of blood products were transfused for malaria. Postpartum hemorrhage (PPH) at 24% (524 of 2228) and cesarean sections at 22% (485 of 2228) were the most transfused diagnostic categories among the obstetrics and gynecology patients, with abortions and cancer accounting for only 10% and 8% of transfusions, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In neighboring Kenya, blood transfusion is mostly used to treat severe malaria-associated anemia and sickle cell disease, and to replace massive blood loss [8,11]. In Ghana, malaria was reported as the main factor for requirement for blood transfusions in children [18]. However, septicemia (19, 13.6%), sickle cell disease (13, 9.3%), and malnutrition (10, 7.1%) are the most common indications for blood transfusion in Nigerian children [27].…”
Section: Discussionmentioning
confidence: 99%
“…Severe anemia secondary to infections, such as malaria, Leishmania species, and Shistosoma species, is a large health problem in Sudanese children [1315]. While there are published data on blood transfusion in children in other African countries [10,11,1618], there are no published data on blood transfusion in Sudan. Therefore, the current study was conducted to determine the rate of anemic children with WHO indications for blood transfusion, and to describe the indications for blood transfusion the time to blood transfusion and outcome of blood transfusion, in children in Gadatif Hospital in eastern Sudan.…”
Section: Introductionmentioning
confidence: 99%